Integral Transforms with Non-separated Variables and Discontinuous Coefficients - Yaremko, O.E. (Журнал математической физики, анализа, геометрии, 2013)
Multidimensional integral transforms with non-separated variables for discontinuous coefficients problems are constructed in the case where the coefficient discontinuities are on the parallel hyperplanes. Explicit kernel formulas for ideal coupling conditions are obtained. The basic integral transform identity is proved. Сконструированы многомерные интегральные преобразования с неразделенными переменными для задач с разрывными коэффициентами в случае, когда разрывы коэффициентов сосредоточены на параллельных гиперплоскостях. Найдены явные формулы для ядер для случая условий идеального сопряжения. Доказано основное тождество интегрального преобразования.